Pengaturan Sektor Jasa Pendidikan Indonesia Dalam Kerangka Liberalisasi WTO - Rehulina, Rehulina; Putri, Ria Wierma; Putri, Yunita Maya (PROGRESIF: Jurnal Hukum, 2021)
General Agreement on Trade and Servies WTO in the Service sector is regulated in the Doha Round along with 12 other trade sectors which are compromises between developing countries and developed countries. The service trade liberalization regulation in Indonesia has been implemented in law Number 20 of 1999 concerning the National Education System and Law Number 12 of 2012 concerning Higher Education.